Etika Profesi Konselor dalam Layanan Bimbingan Konseling Virtual - Raudatul Jannah; H K Marjo (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to describe the professional ethics of counselors in virtual counseling guidance services. The method used in this research is a literature study with a qualitative descriptive approach. The data sources come from document studies in the form of books and previous research from various references. Furthermore, the data analysis technique used is descriptive analysis. The results of this study indicate that online counseling takes the form of virtual counseling technology, namely, websites, telephone or cell phones, email, video conferencing, chat, instant messaging, computers, and other social networks. The ethical aspects that must be obeyed by online counselors are building good relationships on the Internet, confidentiality when conducting consultations, legal aspects of telecommunications via the Internet, and licensing. Therefore, online counselors need to be professional in conducting virtual counseling by considering ethics.